Home Anxiety Assessment and Influencing Factors among Adolescent Athletes in Yantai City - Yuxi Chen; Chunming Ye; Yang Lin; Yongjie Ma; Xingyu Zhang; Jiu Wang (MDPI AG, 2024)
Objective: To understand the prevalence of home-related anxiety among adolescent athletes during the novel coronavirus pandemic and to ascertain the factors influencing this anxiety. Methods: We employed cluster sampling to select 1150 adolescent athletes (aged 8-18 years) from six sports training schools in Yantai City, Shandong Province. Mental health status was assessed and recorded. Chi-square tests and multivariable logistic regression were used to analyze the factors contributing to athletes' anxiety. Results: The survey revealed a COVID-19 infection rate of 38.23% (437 individuals) with an anxiety score of 40.98 ± 8.20 and an anxiety detection rate of 11.29% (129 individuals) during the COVID-19 epidemic. Female athletes exhibited a higher anxiety rate of 14.40% compared to 8.40% in male athletes. Multivariate analysis identified female gender as a risk factor for anxiety (OR = 1.64), while participation in aquatics emerged as a protective factor (OR = 0.24, 95% CI: 1.08-2.48). Professional training duration exceeding three years increased anxiety risk (OR = 3.05, 95% CI: 1.67-5.58), as did not seeking help during difficulties (OR = 2.59, 95% CI: 1.33-5.01). Interestingly, parental care was linked to increased anxiety risk (OR = 2.44, 95% CI 1.34-4.44), while care from friends was protective (OR = 0.60, 95% CI: 0.36-1.01), which was possibly due to the pressure associated with parental expectations. Conclusions: Adolescent athletes, particularly females and those with extended training durations, exhibit a heightened susceptibility to anxiety. This study also highlights that athletes who proactively seek assistance during challenging situations tend to experience lower anxiety levels. Additionally, a lack of COVID-19 infection and the involvement of concerned parents contribute to reduced anxiety among these young athletes.